Intervenção em uma ruína no Douro - tradição e contemporaneidade - Maria Teresa Gameira Fagulha (2017)
The present Master's Dissertation "Intervention in a ruin in Douro - tradition andcontemporaneity" takes an approach to the issue of architectural interventions in pre-existences.The motivation of this work was the opportunity to design a small house in a familyplot in Douro, that would revitalize and "disturb" the silence of an abandoned place.Through an analysis and interpretation mainly focused on the concepts of continuityand rupture within the History of recent Architecture, it reavaluates the early criticismabout the Modern Movement, demonstrating that in fact it didn't break with the pastneither underestimated its legacy and the history of the city.The design of a project to recover a house in ruins, whose purpose is its reuse, materializesthe common thread between Theory, References and Project, looking up fora balance between tradition and contemporaneity, which may be able to respond to thecomplexity of the issues raised during its development. It came up the desire of continuingthe existent, taking advantage of its utility to the present, always considering andbalancing the necessary conditions both of the pre-existence and the new needs.The solution purposed is not a "closed" or definite answer to solve the problems ofthis ruin, but rather a possible way to intervene in a pre-existence, balancing Continuityand Rupture.This work intends to make a reflection that finds reasoned responses to the newchallenges and circumstances of the present, showing that conserving and renewing areattitudes that can coexist simultaneously."(...) the architecture of the coming years will be marked by the practice of recovery.Recovery and creation will be complementary and not specialties that can be autonomouslytreated. (...) It will be recognized that the language adapts itself to reality to give it a form.(...) The instruments of recognition of the real are called History, the art of constructingtransformation is called Architecture."